2009
DOI: 10.1111/j.1654-1103.2009.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

The invasive alien plant species Solidago gigantea alters ecosystem properties across habitats with differing fertility

Abstract: Question: Invasive alien plants can affect biomass production and rates of biogeochemical cycling. Do the direction and intensity of such effects depend upon the functional traits of native and alien species and upon the properties of the invaded habitat, with the same alien species having differing impacts in different habitats?Location: Lowlands of Switzerland.Methods: Fourteen grassland and wetland sites invaded by Solidago gigantea and widely differing in biomass production and soil P availability were sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
49
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 57 publications
(86 reference statements)
9
49
2
Order By: Relevance
“…Both plant species increased mycorrhizal frequency but decreased species richness of AMF (Zubek et al unpublished). Our results agree with those of Scharfy et al (2009Scharfy et al ( , 2010 and Quist et al (2014) who found that S. gigantea invasion had no influence or decreased soil respiration, bacterial biomass, or phosphomonoesterase activity but increased fungal biomass and/or fungal:bacterial ratio. S. gigantea litter may support fungal rather than bacterial growth as it has lower tissue concentrations of most nutrients and higher C:N ratio than adjacent native vegetation Thorn and Lynch 2007;Dassonville et al 2008).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Both plant species increased mycorrhizal frequency but decreased species richness of AMF (Zubek et al unpublished). Our results agree with those of Scharfy et al (2009Scharfy et al ( , 2010 and Quist et al (2014) who found that S. gigantea invasion had no influence or decreased soil respiration, bacterial biomass, or phosphomonoesterase activity but increased fungal biomass and/or fungal:bacterial ratio. S. gigantea litter may support fungal rather than bacterial growth as it has lower tissue concentrations of most nutrients and higher C:N ratio than adjacent native vegetation Thorn and Lynch 2007;Dassonville et al 2008).…”
Section: Discussionsupporting
confidence: 82%
“…Presumably the influence of fluvial processes we had expected in the river floodplain was too weak to alter soil properties as well as plant species richness and cover considerably. Dassonville et al (2008) and Scharfy et al (2009) found that the direction and magnitude of changes in soil properties induced by invasion differed between study sites, but their sites showed differences in initial (preinvasive) soil properties. Specifically, invasion increased nutrient concentrations of surface soils with initially low nutrient concentrations, while under the opposite conditions a negative impact was mainly observed (Dassonville et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations